Grain legume impacts on soil biological processes in Sub-Saharan Africa - Lupwayi, N.Z.; Kennedy, AC; Chirwa, Rowland (2011)
Grain legumes occupy about 20 million hectares in Africa. The major crops are cowpea (Vigna unguiculata L.), which is grown on about 11 million hectares mostly in West Africa, and common bean (Phaseolus vulgaris L.), grown on about 5 million hectares mostly in eastern and southern Africa. These grain legumes have impacted soil organisms, including nitrogen fixers, mycorrhizae, fauna, and the processes that they perform. The legume-Rhizobiumsymbiosis results in dinitrogen (N2) fixation that adds plant-available nitrogen to the soil system. Some of the fixed N2 is recycled when legume crop residues decompose for the benefit of non-legume crops grown with or after grain legumes. This N recycled by grain legumes is minimal because most of the N in these legumes is in the grain that is removed from the farm at harvest. Non-legume crops grown in rotation with legumes may also benefit from endophytic rhizobia. Mycorrhizal associations that improve plant nutrient and water uptake also benefit from the legume in a cropping system. Besides breaking pest cycles, grain legume crops also reduce disease infestation of non-legume crops by enhancing biological pest control through increased microbial diversity and activity. Legumes may contribute to greenhouse gas (nitrous oxide and carbon dioxide) emissions during nitrification and denitrification of fixed N2. However, because less fertilizer N is used in legume-based cropping systems, overall greenhouse gas emissions are usually less than those in fertilized monoculture cereals. Through their effects on soil biology, legume crops also improve soil structure by enhancing the formation and maintenance of soil aggregates. Therefore, grain legumes in Sub-Saharan Africa have positive effects on agriculture by adding and recycling biologically fixed N2, enhancing nutrient uptake, reducing greenhouse gas emissions, and improving soil structure and breaking non-legume crop pest cycles.